PERLINDUNGAN KONSUMEN DALAM TRANSAKSI BAY’ AL-SALAM DAN E-COMMERCE (Komparasi Hukum Islam dan Hukum Positif) - Syaichoni, Ahmad (Ahkam: Jurnal Hukum Islam, 2015)
In the modern era, people utilize technology product to ease the transaction process, namely e-business or e-commerce. Business always includes the producers and consumers. In such business, the consumers do not get maximum service and sometimes are fooled by the producers. Such kind of business in Islam is known as bay’ al salam. The transaction in bay’ al salam is prone to tricky acts by the producers. Therefore, it is urgent to develop a legal contract between the producers and consumers to obtain good transaction between the two parties. Kata kunci: Perlindungan Konsumen, Bay’ al-Salam, E-Commerce, Hukum Islam, dan Hukum Positif